Trade, finance, and development in Pakistan - Andrus, J. Russell; Mohammed, Azizali F. (Karachi : Oxford University Press, 1966)
This book examines trade, finance and development in Pakistan and comprise of the topics like: production and marketing of export crops; foreign trade; balance of payments; central banking; commercial banking; agricultural credit; capital market, price trends; federal finance; and development planning.
Includes index.
Includes bibliographical references: p. 281-283.
lje 28/09/2018
Loans
Keywords: Finance, Public; Economic development; Agriculture; Balance of payments; International trade; Pakistan